Analysis of the effectiveness of Peruvian public policy for COVID-19 containment and economic reactivation - Reyna Motta, Diana Milagros; Coronado Díaz, Miguel Angel; Vargas Salazar, Ivonne Yanete (Política y Sociedad, 2026)
Peru has experienced one of the greatest health and economic crises of all time since the arrival of COVID-19 in March 2020, having arranged the implementation of measures to mitigate the effects of the coronavirus, which were established in two stages: containment and economic reactivation. The objective of this article is to evaluate the effectiveness of public policies implemented for the containment of COVID-19 and economic reactivation of Peru. The methodology was analytical and descriptive based on bibliographic and documentary research, exploring indexed databases, specialized literature and information available on government platforms. The results show serious deficiencies in public management that include low levels of budget execution. In conclusion, based on this experience, it is necessary to strengthen health care, equipment, furniture and infrastructure; which will allow us to be prepared for a new health crisis that represents a threat to life.